2011
DOI: 10.1158/0008-5472.can-10-1855
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Collagen I Promotes Gemcitabine Resistance in Pancreatic Cancer through MT1-MMP–Mediated Expression of HMGA2

Abstract: One of the hallmarks of human pancreatic ductal adenocarcinoma (PDAC) is its pronounced type I collagenrich fibrotic reaction. Although recent reports have shown that the fibrotic reaction can limit the efficacy of gemcitabine chemotherapy, the underlying mechanisms remain poorly understood. In this article, we show that the type I collagen allows PDAC cells to override checkpoint arrest induced by gemcitabine. Relative to cells grown on tissue culture plastic, PDAC cells grown in 3-dimensional collagen microe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
143
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 47 publications
(55 reference statements)
4
143
1
Order By: Relevance
“…After 72 h, cells were extracted from the gels using collagenase and lysed in radioimmune precipitation assay buffer containing protease and phosphatase inhibitors for Western blotting (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…After 72 h, cells were extracted from the gels using collagenase and lysed in radioimmune precipitation assay buffer containing protease and phosphatase inhibitors for Western blotting (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Fedele and colleagues reported that the interaction between HMGA2 and pRb enhanced the activity of E2F1 in pituitary tumorigenesis (25). pRb was a well-known repressor for E2F1 function.…”
Section: The Interaction Between Hmga2 and Prb Facilitates The Transcmentioning
confidence: 99%
“…4F). We then constructed a truncated Flag-tagged HMGA2 which could not interact with pRb (25), and established SGC7901 subline with stable expression of truncated HMGA2 (Fig. 4G).…”
Section: The Interaction Between Hmga2 and Prb Facilitates The Transcmentioning
confidence: 99%
See 1 more Smart Citation
“…Many protein precursors such as matrix metalloproteases, hormones, growth factors, serum proteins, receptors, and adhesion molecules have identified the Furin substrates (Fujisawa et al, 2004;Louagie et al, 2008;Yana and Weiss, 2000). MT1-MMP proenzyme cleavage by Furin is considered to be a principal event in the activation of this substrate and it may be important in HCC cell migration and invasion (Dangi-Garimella et al, 2011).…”
Section: Introductionmentioning
confidence: 99%